Zaposlitvene možnosti kineziologov - Zendzianowsky, Laura (Šport (Ljubljana), 2022)
We researched the employment trends of kinesiologists in Slovenia and in other countries of the European Union. We wanted to find out what the future of the kinesiologist profession is and where it makes sense to focus as a kinesiologist based on trends.We used the ScienceDirect and Google Scholar datasets for data acquisition. We also had an interview with Julian Berriman, director of the Professional Standards Committee. We found that a negative trend currently prevails in the field of employment of kinesiologists in Slovenia. In 2021 eleven jobs for the profession of kinesiologist were registered at the Institute of the Republic of Slovenia. Most kinesiologists are forced to look for employment in the private sector, and some have started their own business. Projections from the Bureau of Labor Statistics show that the employment possibilities of kinesiologists will increase by 13% between 2020 and 2030. The employment opportunities of kinesiologists will grow faster than for most other professions. The inclusion of kinesiologists in the health care system, the growing awareness of the positive effects of exercise and the involvement of governments and insurance companies in the promotion of a healthy lifestyle will certainly contribute to this. The entire fitness industry has also started to move in the direction of health care, which will also be reflected in the greater demand for educated staff, which undoubtedly includes kinesiologists.
Keywords: kineziologija; Slovenija; šport; zaposlitev; zdravje